2021
DOI: 10.1097/rct.0000000000001222
|View full text |Cite
|
Sign up to set email alerts
|

Monosodium Urate Crystal Deposition in Coronary Artery Plaque by 128-Slice Dual-Energy Computed Tomography: An Ex Vivo Phantom and In Vivo Study

Abstract: ObjectiveMonosodium uric acid (MSU) crystals may accumulate in the coronary plaque. The objective was to assess whether dual-energy computed tomography (DECT) allows for detection of MSU in coronary plaque.MethodsPatients were examined with 128-slice DECT applying a cardiac electrocardiogram-gated and peripheral extremity protocol. Patients were divided into 3 groups: gout (tophi >1 cm in peripheral joints), hyperuricemia (>6.5 mg/dL serum uric acid), and controls. The groups were matched for cardiovascular ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 29 publications
3
13
0
Order By: Relevance
“…These deposits were found in patients with the highest calcium scores. The same results were found by the same group in a similar study separating the control group into hyperuricemic and nonhyperuricemic controls [23]. Our group provided conflicting data from a study of popliteal artery plaques in 126 gout patients and 26 controls, showing that MSU-coded plaques were equally prevalent between groups [24 ▪▪ ].…”
Section: Dual-energy Computed Tomography In Gout: a Growing Body Of E...supporting
confidence: 80%
“…These deposits were found in patients with the highest calcium scores. The same results were found by the same group in a similar study separating the control group into hyperuricemic and nonhyperuricemic controls [23]. Our group provided conflicting data from a study of popliteal artery plaques in 126 gout patients and 26 controls, showing that MSU-coded plaques were equally prevalent between groups [24 ▪▪ ].…”
Section: Dual-energy Computed Tomography In Gout: a Growing Body Of E...supporting
confidence: 80%
“…In recent years, along with the improvement of living standards and changes in diet, the content of serum MSU in the population has been increasing [ 10 ]. At present, most studies on gout using DECT focus on peripheral joints, such as the metatarsophalangeal joint, knee joint, sacroiliac joint, and wrist joint, and there are few studies on the deposition of MSU crystals in the cardiovascular system [ [23] , [24] , [25] ]. Several clinical studies confirmed a correlation between gout and the incidence of CVD [ [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] ].…”
Section: Discussionmentioning
confidence: 99%
“…In a study in 2019, Klauser et al [ 23 ] first proposed that there could be MSU deposition in the coronary arteries and proved this view by autopsy. Then, in 2020, Feuchtner et al [ 24 ] also proved that there was MSU deposition in the coronary arteries by establishing a model of MSU deposition in the coronary artery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the CARDIA study, a cohort of young subjects showed that the elevation of SUA levels might be a biomarker for early atherosclerosis, as assessed by coronary artery calcified plaque and carotid intima-media thickness ( 33 ). A recent study using dual-energy computed tomography detected coronary monosodium uric acid crystal deposition in gout patients ( 34 ). However, some studies showed that higher SUA levels were not significantly linked to a higher rate of cardiovascular mortality in CAD patients.…”
Section: Discussionmentioning
confidence: 99%